Mediating Effects of Information Access on Internet Use and Multidimensional Health Among Middle-Aged and Older Adults: Nationwide Cross-Sectional Study - Liping Fu; Caiping Liu; Yongqing Dong; Xiaodong Ma; Quanling Cai; Dongli Li; Kaisheng Di (JMIR Publications, 2024)
BackgroundWith the exacerbation of population aging, the health issues of middle-aged and older adults have increasingly become a focus of attention. The widespread use of the internet has created conditions for promoting the health of this demographic. However, little is known about the effects of information access in promoting the relationship between internet use and the health of middle-aged and older adults. ObjectiveThis study aims to examine the relationship between internet use and multidimensional health in middle-aged and older adults, as well as the mediating effect of information access. Moreover, this study will explore the relationship between other dimensions of internet use (purposes and frequency) and health. MethodsData were sourced from the China General Social Survey conducted in 2018. Health outcomes, including self-rated, physical, and mental health, were assessed using the 5-level self-rated health scale, the 5-level basic activities of daily living scale, and the 5-level depression scale, respectively. The ordinal logistic regression model was used to examine the relationship between internet use and health among middle-aged and older adults. Additionally, the Karlson-Holm-Breen decomposition method was used to examine the mediation effect of information access. To address endogeneity issues, the two-stage least squares approach was applied. ResultsIn our sample, nearly half (n=3036, 46.3%) of the respondents use the internet. Regression analyses revealed that internet use was positively associated with self-rated health (odds ratio [OR] 1.55, 95% CI 1.39-1.74; P<.001), physical health (OR 1.39, 95% CI 1.25-1.56; P<.001), and mental health (OR 1.33, 95% CI 1.19-1.49; P<.001) of middle-aged and older adults. Various dimensions of internet use positively contribute to health. In addition, information access significantly mediated the relationship between internet use and self-rated health (β=.28, 95% CI 0.23-0.32), physical health (β=.40, 95% CI 0.35-0.45), and mental health (β=.16, 95% CI 0.11-0.20). Furthermore, there were significant differences in the relationship between internet use and health among advantaged and disadvantaged groups. ConclusionsThe study showed that different dimensions of internet use are associated with better self-rated health, better physical health, and better mental health in middle-aged and older adults. Information access mediates the relationship between internet use and health. This result emphasizes the significance of promoting internet access as a means to enhance the health of middle-aged and older adults in China.